Decoy Oligodeoxynucleotides, Polysaccharides, and Targeted Peptide‐Functionalized Gold Nanorods for the Combined Treatment of Rheumatoid Arthritis. Issue 23 (4th November 2018) - Zhang, Nan; Zhang, Shasha; Xu, Chunyu; Fu, Lingling; Liu, Tuanbing; Zhao, Yongxing
Abstract: Autoimmune diseases like rheumatoid arthritis (RA) possess complicated pathogenesis. Therefore, RA is hard to treat by monotherapies in clinical setting. All‐in‐one treatments that target inflamed joints and act efficiently are highly needed. Gold compounds are old anti‐RA therapies and are fabricated into gold nanorods (GNRs) that serve as anti‐RA therapeutics as well as nanocarriers for anti‐inflammatory nucleic acid drug‐NF‐κB‐decoy oligodeoxynucleotides (dODNs). A targeted peptide to vascular cell adhesion molecule‐1 (VCAM‐1) (PVCAM‐1 ) is modified onto the GNRs to facilitate enhanced accumulation of GNRs in inflamed tissues and enhanced cellular uptake of GNRs by inflamed cells. dODNs loaded and PVCAM‐1 modified GNRs (GNRs‐dODN‐PVCAM‐1 ) are covered by polysialic acid (PSA) to protect GNRs‐dODN‐PVCAM‐1 in vivo. Simultaneous GNRs, dODN, and thermotherapy show synergic effect on the reduction of TNF‐α and IL‐6 in inflamed macrophages and blood vessel cells. The simultaneous triple therapy (GNRs‐dODN‐PSA‐PVCAM‐1 +laser) demonstrates excellent anti‐inflammatory efficacy in vitro and in vivo. Abstract : Herein, gold nanorods (GNRs) serve as nanocarriers for anti‐inflammatory dODN, antirheumatic drugs, as well as agents for thermotherapy. Targeted peptides and hydrophilic polysialic acid are modified to GNRs to increase targeting to inflammatory tissues and prolong in vivo circulation. GNRs‐dODN‐PSA‐PVCAM‐1 simultaneously inhibits NF‐κB pathway, absorbs inflammatory proteins, and conducts thermotherapy, which achieves a higher reduction of inflammation.